(untitled) (Książnica Śląska, 2025)
The article is devoted to Stanisław Ligoń’s show Wesele na Górnym Śląsku (The Wedding in Upper Silesia). The premiere of the play took place on January 22, 1930 at the Polish Theatre in Katowice. The author discusses the genesis of the play in detail, setting it in a broad context and reaching back to the beginnings of the popularity of “wedding” as a theme for theatrical works. He points out that in the Ligoń’s play the theme of “wedding” had an additional symbolic dimension – it illustrated the connection of Upper Silesia with the reborn Republic of Poland. The article also describes the play’s premiere and the stage history of the work from the interwar period to the present day.